Studi Living Qur’an Terhadap Pertunjukkan Salawaik Dulang Pada Masyarakat Nagari Singgalang X Koto Tanah Datar - Wassalam, Sabri; Fitri, Aulia; Umairah, Rahmi; Kirin, Arwansyah Bin; Fata, Azamel (Al-Kauniyah, 2025)
Salawaik Dulang is a traditional oral art of the Minangkabau people that presents Islamic verses containing praises to the Prophet Muhammad, prophetic stories, and religious advice accompanied by rhythmic dulang percussion. Although it functions as an important medium of dakwah, this tradition faces challenges from modernization and the declining interest of the younger generation. This study aims to explore the origins, performance processes, and religious values embedded in the Salawaik Dulang tradition in Nagari Singgalang. This field research employs a descriptive-analytic method and utilizes an ethnographic approach within a qualitative research framework. Data were collected through observation, interviews, and documentation, with informants consisting of the Nagari government, Salawaik Dulang performers, religious scholars, traditional leaders, and the local community. The findings indicate that Salawaik Dulang began to develop in Nagari Singgalang in the 1970s, inspired by performance groups from Nagari Pariangan. Its performance structure includes an opening, praises to Allah, the core dakwah delivered through cancan chants, humorous interludes, and a closing containing moral messages. The study also reveals that the religious values in Salawaik Dulang encompass three main pillars: creed (akidah), Islamic law (syariah), and ethics (akhlak). Its verses successfully internalize the teachings of monotheism, love for the Prophet, reminders of the Day of Judgment, and ethical values such as honesty, modesty, and the obligations of worship. Thus, Salawaik Dulang serves as an effective medium of dakwah that strengthens Islamic values in the daily lives of the Nagari Singgalang community.